KEARIFAN LOKAL DAN RADIKALISME: MEMPERKUAT PEMBELAJARAN PAI MELALUI SCIENTIFIC LEARNING - Khalis, Habiba (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2019)
This paper explains about the strengthening of PAI learning through scientific approaches in order to counter radicalism. The rise of the issue of radicalism that is happening, threatens the world of education to be vigilant in giving defense to their students. The effort made is to provide reinforcement in the PAI lessons using a scientific approach. PAI is one of the subjects that has a great opportunity to strengthen students' defenses. With a scientific approach students will not only understand the material but will be able to see objectively what they are learning. The stages in the scientific approach are observing, asking, trying, reasoning, and associating.